Synthesis and characterization of novel functional vinyl ethers that bear various groups - Fayad, Antoinette; El Malti, Wassim; Ameduri, Bruno; Alaaeddine, Ali (Comptes Rendus. Chimie)
The synthesis of new functionalized vinyl ethers (VEs) by transetherification reaction between ethyl vinyl ether (EVE) and different alcohols is presented. An air-stable palladium catalyst generated in situ efficiently catalyzed the reaction leading to various VEs in a single step with good alcohol conversion (50–82%) and good VE yields (up to 75%). The reaction conditions were optimized in terms of the initial EVE/alcohol molar ratio, alcohol concentration, solvent, presence and nature of the ligand, amount of the catalyst, and choice of the metal precursor. All VEs were characterized using $^{1}$H and $^{13}$C NMR spectroscopy.